2008
DOI: 10.1016/j.toxlet.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled ultrafine particulate matter affects CNS inflammatory processes and may act via MAP kinase signaling pathways

Abstract: In addition to evidence that inhalation of ambient particulate matter (PM) can increase cardiopulmonary morbidity and mortality, the brain may also constitute a site adversely effected by the environmental presence of airborne particulate matter. We have examined the association between exposure to PM and adverse CNS effects in apolipoprotein E knockout (ApoE-/-) mice exposed to two levels of concentrated ultrafine particulate matter in central Los Angeles. Mice were killed 24 hr after the last exposure and br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
94
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(99 citation statements)
references
References 29 publications
2
94
1
2
Order By: Relevance
“…Specific toxicological actions include impairment of phagocytosis and breakdown of defence mechanisms, crossing tissues and cell membranes, injury to cells, generation of reactive oxygen species, oxidative stress, inflammation, production of cytokines, depletion of glutathione, mitochondrial exhaustion, and damage to protein and DNA, most of which also occurs with larger size PM (Bakand, Hayes & Dechsakulthorn, 2012). Biodistribution studies also suggest that the effects of ultrafine particles may very well be observed in organs other than those that correspond to the port of entry -for example, the central nervous system (Kleinman et al, 2008;Kreyling et al, 2013). In light of different biodistributions on inhalation and the likelihood that ultrafine particles can escape natural defence mechanisms, such as phagocytosis, it is likely that ultrafine particles will also be linked to biological pathways and responses that differ from larger size particles (fine and coarse PM).…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…Specific toxicological actions include impairment of phagocytosis and breakdown of defence mechanisms, crossing tissues and cell membranes, injury to cells, generation of reactive oxygen species, oxidative stress, inflammation, production of cytokines, depletion of glutathione, mitochondrial exhaustion, and damage to protein and DNA, most of which also occurs with larger size PM (Bakand, Hayes & Dechsakulthorn, 2012). Biodistribution studies also suggest that the effects of ultrafine particles may very well be observed in organs other than those that correspond to the port of entry -for example, the central nervous system (Kleinman et al, 2008;Kreyling et al, 2013). In light of different biodistributions on inhalation and the likelihood that ultrafine particles can escape natural defence mechanisms, such as phagocytosis, it is likely that ultrafine particles will also be linked to biological pathways and responses that differ from larger size particles (fine and coarse PM).…”
Section: Toxicological Studiesmentioning
confidence: 99%
“…Hence, generating innovative strategies for facilitating the targeting of nanoparticle agents across the BBB, while developing a reduced toxicity profile for these agents, remains a challenge in the field. [18][19][20] As a result, the objective of the present in vitro study was to investigate the proper modification for SPIONs for nontoxic brain drug delivery by using an optimized BBB model.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to particulate matter (PM) and in particular, ultrafine particles (UFPs, diameter < 100 nm), have been associated with increasing mortality and morbidity rates by many epidemiological studies (Johnston et al, 2000;Donaldson et al, 2002;MacNee and Donaldson, 2003;Gilmour et al, 2004;Kleinman et al, 2008;Nemmar and Inuwa, 2008;Zuurbier et al, 2011). In an urban area, traffic emissions are the dominant source of UFPs and other air pollutants (Cyrys et al, 2008).…”
Section: Introductionmentioning
confidence: 99%